Laboratory Review for Stabilization of Soil in Kashmir VALLEY by Using Surkhi and Ceramic Tile Waste (International Journal of Innovative Research in Computer Science & Technology, 2022)
Clay soil has been identified as a concern  all around the world due to its swelling and shrinking  qualities when it comes into touch with water. The load  characteristics of soil are particularly low due to this clay  feature. The influence of surkhi and ceramic tile dust on  the geotechnical characteristics of clay soil is investigated  in this study. The main goal of this research is to  investigate the use of surkhi and ceramic tile dust as soil  stabilisers in order to reduce the cost of soil stabilisation.  The varied percentages of surkhi and ceramic tile dust, as  well as their various combinations, were employed. . The  soil at lower proportions of Optimum Water Content since  there was a substantial improvement in Maximum Dry  Density (MDD) (OMC). These materials not only give an  alternative to the use of traditional materials, but they also  aid in the reduction of pollution. Most of the time, these  waste items are dumped in open areas, causing a lot of  problems for the people who live in the region as well as  the professionals who work there. Surkhi and ceramic tile  dust may definitely be regarded an excellent stabilising  element for clayey soil based on the findings.
Keywords: Ceramic tile dust; Stabilization; Maximum Dry Density; Optimum Moisture Content; Surkhi